1992
DOI: 10.1159/000116858
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Multiple-Dose Pharmacokinetics of Controlled-Release Levodopa Products

Abstract: The multiple-dose (200 mg levodopa t.i.d.) pharmacokinetic profile of two controlled-release products of levodopa (Madopar® HBS and Sinemet® CR) was compared to conventional Madopar capsules in 18 healthy volunteers in a cross-over, randomized design. A pronounced controlled-release profile of the Madopar HBS and Sinemet CR product was demonstrated compared to conventional Madopar capsules with a significant (p < 0.001) decrease (-40 and -55%) in Cmax and a significant (p < 0.001) increase (+237 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Overall, the pharmacokinetic findings of levodopa and 3-O-methyldopa in this study are in good agreement with multiple-dose data reported previously for Madopar DR [27]and Madopar HBS [17, 27]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, the pharmacokinetic findings of levodopa and 3-O-methyldopa in this study are in good agreement with multiple-dose data reported previously for Madopar DR [27]and Madopar HBS [17, 27]. …”
Section: Discussionsupporting
confidence: 92%
“…In healthy volunteers, daily doses of 600 mg (200 mg t.i.d.) of levodopa in the form of Madopar HBS resulted in a high incidence of adverse events probably related to drug administration such as nausea and vomiting [17]. The rationale of the present dosage regimen is based on therapeutic practice in parkinsonians and reduction in the incidence of adverse events previously observed in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…This value is similar to that reported by Deleu et al (1991) in dogs. The values found in men ranged from 30 min to 2 h (Bredberg et al, 1990, Grahnen et al, 1992, Contin et al, 1993.…”
Section: Discussionmentioning
confidence: 98%
“…The biphasic release properties of the new formulation allow a relatively early peak concentration to be attained which subsequently is maintained within the therapeutic concentration range for several hours. The peak concentration is attained more rapidly than with conventional slow-release formulations such as Madopar ® HBS and Sinemet ® CR [19]. To reduce the incidence of adverse events, it is usually advised to administer levodopa-containing formulations after a meal.…”
Section: Discussionmentioning
confidence: 99%